TINJAUAN TENTANG PENGGUNAAN TRAVEL WITH PURPOSE (TWP) BOTTLE SEBAGAI ROOM AMENITIES DI HILTON HOTEL BANDUNG - Mardiah, Fitriatum; Della Sari, Windy; Rochanawati, Ida; Husna, Rifdatul (Akademi Pariwisata Bunda Padang, Sumatera Barat, Indonesia, 2023)
This article reports the results of a study on the use of Travel With Purpose (TWP) Bottle as room amenities in the housekeeping department. Data obtained through documentation, interviews, observation, and questionnaires. Travel With Purpose (TWP) Bottle is Hilton's Environmental, Social and Governance (ESG) strategy to drive responsible travel and tourism globally. Through Travel With Purpose, we strive to create a positive environmental and social impact across operations, supply chains and communities. To support the operational continuity of the Travel With Purpose (TWP) Bottle, the housekeeping department it self sets standard operational procedures, namely standard operational procedures for the sanitation process for washing bottles and standard operational procedures for water refills for refilling which are carried out every day. Apart from that, through the use of Travel With Purpose (TWP) Bottle it can also reduce waste, especially plastic bottles, also compared to using disposable bottles, using refillable Travel With Purpose (TWP) Bottle can minimize costs in the housekeeping department because they have the most affordable prices.